Islamic Banking in Malaysia: Past, Present and Future - Joni Tamkin Borhan (Studia Islamika, 2003)
This paper will discuss the historical development of establishment of Islamic banking in Malaysia, their operations and application of Islamic Commercial Law's principles in the Malaysian Islamic banking system. This paper will also elaborates the challenges and some issues which are being faced by Malaysian Islamic banking system and its prospects in the future.DOI: 10.15408/sdi.v10i2.630